Predstavitev organiziranosti športne vzgoje na Ekonomski fakulteti Univerze v Ljubljani - Zovko, Vinko (Šport (Ljubljana), 2019)
As regular sporting activity is one of the most important building blocks of a healthy lifestyle, we decided that sports education at the Faculty of Economics will be compulsory for all students in the first year and voluntary for all students in senior years. We also set up a virtual sports class that includes students who have an athlete status in the current academic year. The latter is led by the co-called coordinator for the sports class, who is also a professor at the faculty.
Keywords: Ekonomska fakulteta; Faculty of Economics; physical education; Slovenia; Slovenija; sport; student sport; students; šport; športna vzgoja; študentje; študentski šport; University of Ljubljana; Univerza v Ljubljani